The Role of United Nations High Commisioner for Refugees (Unhcr) in Handling Cases of Afghanistan Refugees During the Covid-19 Pandemic in Indonesia - Alamsyah, Jahhid Fitrah; Harahap, Ali Musa (UNIDA GONTOR, 2023)
This research aims to analyze the impact of the COVID-19 pandemic on Afghan refugees in Indonesia and the role played by the United Nations High Commissioner for Refugees (UNHCR) in meeting their needs. The COVID-19 pandemic has had a significant impact on international refugees. Many countries are restricting the movement of people and tightening screening for those entering, making it difficult for refugees to get protection and assistance. Refugees also often have limited access to health and safety services, exacerbating an already difficult situation. International refugee organizations such as UNHCR work to help refugees through these situations, for example by facilitating access to health services and providing financial assistance. However, limited resources and changing regulations complicate these efforts. This research aims to find out the role of UNHCR in handling Afghan refugees during the COVID-19 pandemic in Indonesia as well as indicative data in strengthening the facts about the role of UNHCR Indonesia. This research uses qualitative data collection methods such as in-depth interviews and focus group discussions to gather information from Afghan refugees and relevant stakeholders. This research also uses the perspective of Human Rights, Individual Security, and the concept of International Organization. Broadly speaking, the result of this research is to provide an explanation of the role provided by UNHCR in the form of protection, advocating for the provision of health facilities, providing educational facilities and providing temporary shelter. The findings of this study contribute to a better understanding of the role provided by UNHCR to refugees during the COVID-19 pandemic and the effectiveness of UNHCR's response in meeting their needs.